The Relationship Of The Age Of Pregnant Women Under 20 Years Old With Premature Delivery - Efi Satriana Silalahi (International Archives of Medical Sciences and Public Health, 2020)
Introduction: There are still many preterm labourers from the age factor of the mother, namely, women who become pregnant at the age of 20 years greatly affects the occurrence of preterm labour. Pregnant women under 20 years old can harm maternal health as well as the growth and development of the fetus because of the immature reproductive apparatus for pregnancy and coupled with psychological, social, and economic stress, thus facilitating the occurrence of prematurity. This study aims to analyze the relationship between the age of pregnant women under 20 years old and premature delivery at the Muhammadiyah General Hospital Medan.. Method: This type of research is an analytical survey with a cross-sectional approach. The population in this study was all maternity mothers who gave birth at the Muhammadiyah Medan General Hospital, which amounted to 43 people. The sample was 43 people with a sampling technique, namely a total sampling where the entire population was sampled. Data were obtained by interview using questionnaires and analysis with chi-square. Result : Spearman, there is that Probability (0.001) < ? (0.05) means Ho rejected, meaning that it is seen that the age of pregnant women under 20 years of age is significantly related to premature delivery. It is expected for health workers to be able to provide information by conducting counselling to mothers who are pregnant under the age of 20 years about the impact/risk that occurs in their pregnancy.